4(x-1)=-5(x+3)+32

Simple and best practice solution for 4(x-1)=-5(x+3)+32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-1)=-5(x+3)+32 equation:


Simplifying
4(x + -1) = -5(x + 3) + 32

Reorder the terms:
4(-1 + x) = -5(x + 3) + 32
(-1 * 4 + x * 4) = -5(x + 3) + 32
(-4 + 4x) = -5(x + 3) + 32

Reorder the terms:
-4 + 4x = -5(3 + x) + 32
-4 + 4x = (3 * -5 + x * -5) + 32
-4 + 4x = (-15 + -5x) + 32

Reorder the terms:
-4 + 4x = -15 + 32 + -5x

Combine like terms: -15 + 32 = 17
-4 + 4x = 17 + -5x

Solving
-4 + 4x = 17 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-4 + 4x + 5x = 17 + -5x + 5x

Combine like terms: 4x + 5x = 9x
-4 + 9x = 17 + -5x + 5x

Combine like terms: -5x + 5x = 0
-4 + 9x = 17 + 0
-4 + 9x = 17

Add '4' to each side of the equation.
-4 + 4 + 9x = 17 + 4

Combine like terms: -4 + 4 = 0
0 + 9x = 17 + 4
9x = 17 + 4

Combine like terms: 17 + 4 = 21
9x = 21

Divide each side by '9'.
x = 2.333333333

Simplifying
x = 2.333333333

See similar equations:

| -60x+32=Qx+p | | 5x+(2x-2)-(4x-3)= | | 3w+15=18 | | 3xy+9xy-5xy= | | 3(x-3)+2(x+2)=40 | | Y=4x^3-3x^2 | | F(x)=x^3-4x^2-5x | | 7(p+2)=-4(-4p-8) | | -2(5x+1)=-3-3x | | 3(5n-5)=-90 | | 9c=5(101)-160 | | z-10=28 | | -8(4x-3)+6x=-158 | | -8(3x+1)+5x=87 | | 91=7(-5a-2) | | 2n/3=11 | | -6(3x+5)=60 | | (9*9)-(8+4)= | | -6k+15=-5k+2k | | -10-(-63)= | | -117+4x=12x+107 | | (-5)+x=32 | | 900t-10t^2=0 | | 4(5-4x)-3x=96 | | 2(5-2x)=1.2(3x-5) | | 4(5-4x)-3x=97 | | -6(3x+4)=30 | | 2u-9=-7u | | Tan63=X/4 | | 10x-93=-x+94 | | 3+.05(4a+8)=9-2a | | F(x)=12x-2y |

Equations solver categories